Avaliação da resposta tecidual e mineralização de dois materiais experimentais a base de mta para endodontia em dentes decíduos - Silva, Leopoldo Cosme (2017)
The development of biocompatible materials for indication in endodontic therapy of primary teeth is of fundamental importance. Modifications have been proposed to mineral aggregate trioxide (MTA) to obtain a material with better properties for use in pulpotomy of deciduous teeth (MEPulpo-MTA) and a material to be used to obturate root canals of the deciduous dentition (MEPulpect-MTA) . The objective of this study was to evaluate the biological behavior and the deposition of mineralized structures of these materials and to compare them to the MTA. Thirty male rats were used, which were divided into 4 groups: 1: MEPulpo-MTA-Angelus®; 2: MEPulpect-MTA-Angelus®; 3: Conventional MTA-Angelus®; 4: Control - empty tube. Each animal received 4 implants in the subcutaneous, 3 tubes with different materials and 1 empty tube (control). After the periods of 7, 15, 30, 60 and 90 days the animals were euthanized and processed for inclusion in historesin. The cuts obtained from the subcutaneous implants were stained with hematoxylin and eosin for morphological and morphometric analysis of the inflammatory cells, and submitted to Von Kossa and Polarized Light for identification of mineralized structure. The results were submitted to the normality test of Shapiro-Wilk and when they passed the normality test the ANOVA test was performed, followed by the Tukey test and when they did not go through normality, Kruskal-Wallis followed the Dunn's test. Values of p <0.05 were considered significant. In the count of infammatory cells at 7 and 15, there was a statistically significant difference between MEPulpo-MTA and MTA, where the inflammatory infiltrate was higher for MEPulpo-MTA and at 30, 60 and 90 days there was no statistically significant difference between them (p <0, 05). In all periods, there was a mineralized structure formation for MTA and MEPulpo-MTA detected by the Von Kossa method, which presented a statistically significant difference between the materials only at 90 days (Kossa marking and birefringent structures at Polarized Light were positive in all materials tested and at all times analyzed. It can be concluded that MEPulpo-MTA presented characteristics of biocompatibility and deposited mineralized structures similar to MTA. MEPulpect-MTA showed areas of mineralization similar to MTA, but not well tolerated by the tissue.